1000HPK Training For Cadres and Pregnant Women To Prevent Stunting In The Bungursari Health Center Work Area Of Tasikmalaya City In 2020 - Melsa Sagita Imaniar; Rissa Nuryuniarti; Sri Wahyuni Sundari; Wiatanti Wiatanti; Hikmatunnisa Hikmatunnisa (AbdimasMu UMTAS, 2022)
Bungursari Health Center in 2018 had stunting toddlers as many as 219 out of 1140 toddlers (19%). In 2018 there were 28 stunted toddlers with chronic malnutrition conditions, as well as pregnant women who experienced KEK as many as 23 people, as many as 56% of mothers who breastfeed exclusively and mothers as much as 74% have provided complementary breast milk since the age of 4 months and many mothers provide breast milk companion food with a menu that does not meet the STANDARD 4 quadrant WHO. This community service aims to carry out 1000 HPK mentoring training for cadres so that there is an increase in the knowledge and skills of cadres in escorting 1000 HPK so as to prevent stunting. Community Service training of 1000 HPK followed by 30 cadres for 2 days involving expert sources in their fields, namely the Head of Health Center, Midwife Coordinator, Nutritionist and Promkes and Midwife with the expertise of breastfeeding counselors, training is carried out face-to-face question and answer discussion methods and practicums. The results of the activities obtained are in the improvement of the knowledge and skills of cadres in controlling 1000 HPK.